Trends and Practices in Tonsil Surgery—A National Survey for Otorhinolaryngologists - Uusitalo, Tapani; Sakki, Anniina; Laajala, Aleksi; Jero, Jussi; Nokso-Koivisto, Johanna; Piitulainen, Jaakko (Wiley, 2025)
Objectives: To study the changes in tonsil surgery practice over a 10-year period and to survey opinions about its current use and future practice among Finnish otorhinolaryngologists.
Methods: An online survey was distributed between January and March of 2021 to otorhinolaryngologists in Finland.
Results: Altogether, 203 surveys were available for the analysis. Partial tonsil surgery has become the main surgical method, based on 75% of responders, for tonsillar hypertrophy in children over a 10-year period. A similar change did not exist in adults and for infectious indications, but the attitudes support change. The most common surgical technique was monopolar electrocautery and cold-steel dissection for extracapsular tonsillectomy and monopolar electrocautery and coblation for tonsillotomy. In choosing the method for tonsil surgery, the most important factors were the efficiency of symptom relief, familiarity, and avoidance of complications. In surgical practice, influencing a surgeon's choice the most was their residency experience, colleagues, and personal experience. A rather high percentage of opioid prescription (23%) after partial tonsil surgery was noted.
Conclusion: Here, in children, we report a paradigm shift toward partial tonsil surgery occurring within 10 years in the treatment of tonsillar hypertrophy. We also show that opinions support that this change may be used for adults and for infectious indications. A wide variety in tonsil surgery instruments ranging from newer techniques (e.g., coblation) to cold steel existed. Local practice strongly influenced the surgeon's choice.
Level of evidence: N/A.